Response of cytoplasmic pH to anoxia in plant tissues with altered activities of fermentation enzymes: application of methyl phosphonate as an NMR pH probe. - Couldwell, D; Dunford, R; Kruger, N; Lloyd, D; Ratcliffe, R; Smith, A (2009)
BACKGROUND AND AIMS: Acidification of the cytoplasm is a commonly observed response to oxygen deprivation in plant tissues that are intolerant of anoxia. The response was monitored in plant tissues with altered levels of lactate dehydrogenase (LDH) and pyruvate decarboxylase (PDC) with the aim of assessing the contribution of the targeted enzymes to cytoplasmic pH (pH(cyt)) regulation. METHODS: The pH(cyt) was measured by in vivo (31)P nuclear magnetic resonance (NMR) spectroscopy using methyl phosphonate (MeP) as a pH probe. The potential toxicity of MeP was investigated by analysing its effect on the metabolism of radiolabelled glucose. KEY RESULTS: MeP accumulated to detectable levels in the cytoplasm and vacuole of plant tissues exposed to millimolar concentrations of MeP, and the pH-dependent (31)P NMR signals provided a convenient method for measuring pH(cyt) values in tissues with poorly defined signals from the cytoplasmic inorganic phosphate pool. Pretreatment of potato (Solanum tuberosum) tuber slices with 5 mm MeP for 24 h did not affect the metabolism of [U-(14)C]glucose or the pattern of (14)CO(2) release from specifically labelled [(14)C]-substrates. Time-courses of pH(cyt) measured before, during and after an anoxic episode in potato tuber tissues with reduced activities of LDH, or in tobacco (Nicotiana tabacum) leaves with increased activities of PDC, were indistinguishable from their respective controls. CONCLUSIONS: MeP can be used as a low toxicity (31)P NMR probe for measuring intracellular pH values in plant tissues with altered levels of fermentation enzymes. The measurements on transgenic tobacco leaves suggest that the changes in pH(cyt) during an anoxic episode are not dominated by fermentation processes; while the pH changes in the potato tuber tissue with reduced LDH activity show that the affected isozymes do not influence the anoxic pH response.